2019
DOI: 10.1038/s41598-019-54172-4
|View full text |Cite|
|
Sign up to set email alerts
|

Structure, optical and magnetic properties of new Bi0.5Na0.5TiO3- SrMnO3−δ solid solution materials

Abstract: The new Bi0.5Na0.5TiO3-SrMnO3−δ solid solution materials were fabricated via sol–gel method. The random incorporation of Sr and Mn cations into host lattice of Bi0.5Na0.5TiO3 resulted in structural distortion and influenced on the reduction of the optical band gap from 3.07 eV to 1.81 eV for pure Bi0.5Na0.5TiO3 and 9 mol% SrMnO3−δ solid solution into Bi0.5Na0.5TiO3. The magnetic properties of Bi0.5Na0.5TiO3 materials at room temperature were tuned via compensation of diamagnetic material with weak-ferromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…However, unlikely Na-vacancies, the O-vacancies were predicted to be agent of the nonmagnetic moment 30 . The O-vacancies were important in promoting the reduction in valence state from Ti 4+ to Ti 3+ (even Ti 2+ ) because of oxygen vacancies bounding surround 30 , 31 , 74 76 . The theorey predicted that Ti 4+ has no magnetic moment whereas the Ti 3+ or Ti 2+ have nonzero magnetic moment 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlikely Na-vacancies, the O-vacancies were predicted to be agent of the nonmagnetic moment 30 . The O-vacancies were important in promoting the reduction in valence state from Ti 4+ to Ti 3+ (even Ti 2+ ) because of oxygen vacancies bounding surround 30 , 31 , 74 76 . The theorey predicted that Ti 4+ has no magnetic moment whereas the Ti 3+ or Ti 2+ have nonzero magnetic moment 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the enhancement in O-vacancies were indirectly induced by the magnetic moment along with the contribution of magnetization of Ti 3+/2+ defects, resulting in increased magnetic moment that were over the self-defects compared with pure Na 0.5 Bi 0.5 TiO 3 samples. Recently, XPS results have shown that the Ti 4+ cations in Na 0.5 Bi 0.5 TiO 3 materials were possible reduced to Ti 3+ via modification of CaFeO 3−δ - and SrMnO 3−δ -modified as solid solution 30 , 31 . Therefore, we suggested that the increasing the O-vacancies was promoted by the magnetization of self-defect of Ti 3+ cations.…”
Section: Resultsmentioning
confidence: 99%
“…SrMnO 3 has two stable phases; high temperature cubic phase and low temperature hexagonal phase. Between these two phases, hexagonal phase is more stable in oxygen stoichiometric condition [4,7,8]. It is revealed that early first transition metal oxides (Ti, V) show on site d-d Coulomb repulsion energy (U) lesser than the charge transfer energy between ligand p to metal d orbital (Δ), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For the perfect BNT (110) surface, the absorption unit italicαhνn is almost equal to zero in the low photon‐energy region and increases rapidly in the high photon‐energy region. These characteristics were correspondent with the bulk rhombohedral BNT 12,13,17,23,27 . Compared with the perfect surface, the absorption boundary of each BNT (110) with defects seems substantially extended toward the low photon‐energy region.…”
Section: Resultsmentioning
confidence: 58%
“…The calculation for surface energy among the (010), (100), (101) and (111) surfaces indicated that the (100) surface is the most stable of the four kinds of surfaces 11 . However, the calculation for the (100) BNT surface direction was not consistent with the experimental results given in Refs [10–15], where the BNT (110) direction was favoured for crystal growth. Thus, we suggested that the observed room‐temperature ferromagnetism in BNT materials could be contributed by BNT (110)‐surface defects rather than that of (100)‐surface defects.…”
Section: Introductionmentioning
confidence: 58%